Criminal Offence of Dumping Pig Carcasses into the Sea Based on Unlawful Acts - Prabowo, Agung; Pello, Jimmy; Dede, Ngongo (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study examines the criminal aspects of dumping pig carcasses into the sea in East Flores. This phenomenon has significant ecological and social impacts. Purposes of the Research: The purpose of the research is to analyze the application of the concept of criminal law in the case and identify obstacles to law enforcement. Methods of the Research: Using normative-empirical research methods with a case study approach, data was collected through document studies and interviews with authorities. Findings of the Research: The results of the study show that the act of dumping pig carcasses into the sea in East Flores has met the elements of criminal law, especially related to criminal law. The results of the study show that the act of dumping animal carcasses into the sea meets the elements of illegal acts because it causes environmental pollution, threatens public health, and damages marine ecosystems and coastal economic activities. This act is contrary to the Environmental Protection and Management Law, the Marine Law, and regulations on animal health. Perpetrators can be held criminal, civil, and administrative liable in accordance with applicable legal provisions. However, law enforcement faces challenges such as: lack of public awareness, difficulty in proof. This research contributes to the understanding of the existence and application of environmental criminal law in coastal areas